The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10802-012-9620-0
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and PTSD Symptoms

Abstract: PTSD symptoms related to school bullying have rarely been investigated, and never in national samples. We used data from a national survey to investigate this among students from grades 8 and 9 (n = 963). The prevalence estimates of exposure to bullying were within the range of earlier research findings. Multinomial logistic regression showed that boys were 2.27 times more likely to be exposed to frequent bullying than girls. A latent variable second-order model demonstrated an association between frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
82
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 66 publications
12
82
2
6
Order By: Relevance
“…Após análises estatísticas, os autores perceberam que dois tipos de bullying, vitimização direta e relacional, estavam relacionadas positivamente e significativamente aos sintomas de TEPT. Idsoe et al (2012) realizaram uma pesquisa com 963 estudantes de uma amostra representativa de crianças norueguesas das séries 8-9 (13 e 14 anos aproximadamente), para investigar a vitimização por bullying e associações com sintomas de TEPT. Como resultados principais, os autores constataram que havia uma associação entre a frequência de exposição a bullying e sintomatologia de TEPT, sendo que 33,7% dos estudantes que sofreram bullying apresentaram escores significativos para o transtorno.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Após análises estatísticas, os autores perceberam que dois tipos de bullying, vitimização direta e relacional, estavam relacionadas positivamente e significativamente aos sintomas de TEPT. Idsoe et al (2012) realizaram uma pesquisa com 963 estudantes de uma amostra representativa de crianças norueguesas das séries 8-9 (13 e 14 anos aproximadamente), para investigar a vitimização por bullying e associações com sintomas de TEPT. Como resultados principais, os autores constataram que havia uma associação entre a frequência de exposição a bullying e sintomatologia de TEPT, sendo que 33,7% dos estudantes que sofreram bullying apresentaram escores significativos para o transtorno.…”
Section: Resultsunclassified
“…Como resultados principais, os autores constataram que havia uma associação entre a frequência de exposição a bullying e sintomatologia de TEPT, sendo que 33,7% dos estudantes que sofreram bullying apresentaram escores significativos para o transtorno. Segundo Idsoe et al (2012), os resultados indicam que a exposição ao bullying é um potencial fator de risco para o desenvolvimento de sintomas de TEPT entre os estudantes vitimizados.…”
Section: Resultsunclassified
“…The few studies that have been conducted yield results that suggest that bullying although not in line with the DSM criteria for PTSD does significantly increase the risk of a PTSD diagnosis. In a Norwegian national sample of 8 th and 9 th graders it was found that 27.6% of boys and 40% of boys who had been bullied met criteria for PTSD [51]. Bullying could be perceived as more threatening in Uganda than in Europe due to the emphasis placed on family and group for survival.…”
Section: Cross Cultural Comparison Of Direct Exposure To Potentially mentioning
confidence: 99%
“…As additional reason, abuse experiences also seem to be an important risk factor for psychosis [65,66], since individuals with ASD are at an elevated risk for abuse [67,68] and report physical abuse (19%) in their childhood [69] or sexual abuse (40%) in women with higher levels of autistic traits [68]. Posttraumatic stress disorder (PTSD) often results from psychological trauma, such as childhood experiences with bullying and abuse [70][71][72]. Interestingly, the prevalence of PTSD is also higher (11% to 17%) in individuals with ASD [10, 68,73] than in the general population (0.3% to 6.1%) [74].…”
Section: Introductionmentioning
confidence: 99%